Pengembangan Alat Peraga Pita Perkalian Pada Pembelajaran Matematika Dengan Pendekatan Saintifik di MI Miftahul Ulum Cermenan Jombang - Ali Mahsun (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Mathematics basically has basic abstract objects, which in the process of learning mathematics for children aged 7-12 years need the help of concrete objects that can be manipulated, thus helping students understand the material easily and create fun learning, especially multiplication material. So in this study, researchers developed the Multiplication Tape props for grade III students of Madrasah Ibtidaiyah. This research uses the R & D (Research and Development) design model of the Borg & Gall development model by taking 8 stages namely, potential and problems, collecting data, product design, design validation, design revisions, product trials, product revisions, trial use . Based on product development, validation results obtained, i.e. design validation obtained 80% value in the valid category, material expert validation obtained 100% value in the highly valid category, and learning expert validation obtained 72.7% in the valid category. Whereas in large group trials based on student assessments, the score was 93.3% in the excellent category. Thus it can be concluded that the Education Multiplication Props are effectively utilized in the learning process.